2015
DOI: 10.1021/np500626x
|View full text |Cite
|
Sign up to set email alerts
|

Armochaetoglobins A–J: Cytochalasan Alkaloids from Chaetomium globosum TW1-1, a Fungus Derived from the Terrestrial Arthropod Armadillidium vulgare

Abstract: Ten new cytochalasan alkaloids, termed armochaetoglobins A-J (1-10), and four known chaetoglobosins (11-14) were isolated from a methanol extract of Chaetomium globosum TW1-1, a fungus isolated from the medicinal terrestrial arthropod Armadillidium vulgare. Their structures were elucidated by a combination of spectroscopy, single-crystal X-ray crystallography, and ECD calculations. Armochaetoglobins A-E (1-5) represented the first examples of seco-chaetoglobosins arising from an oxidative cleavage of C-19 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…The structures of compounds 3 – 9 were established by comparison with the published data as chaetoglobosin G [26], chaetoglobosin F [6,27], chaetoglobosin C [6], chaetoglobosin A [6], chaetoglobosin E [6], armochaetoglobosin I [28], and cytoglobosin C [29]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of compounds 3 – 9 were established by comparison with the published data as chaetoglobosin G [26], chaetoglobosin F [6,27], chaetoglobosin C [6], chaetoglobosin A [6], chaetoglobosin E [6], armochaetoglobosin I [28], and cytoglobosin C [29]. …”
Section: Resultsmentioning
confidence: 99%
“…This deduction could also be concluded by comparison of the cytotoxic activities between compounds 3 and 7 . In previous investigations, the known chaetoglobosins covered in the study had shown cytotoxicity against many different human cancer cell lines [15,16,27,28,29,32,33]. To our best knowledge, there were no previous reports on the cytotoxicity of these chaetoglobosins to MDA-MB-435, A549 and SGC-7901 cell lines, except compounds 8 and 9 , which were tested on the A549 cell line [28,29] with IC 50 values almost identical to our current results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the complete structure of 1 was established and accordingly assigned as 6-O-methyl-chaetoglobosin Q, which was probably obtained as an artifact from acidic solvolisis of the epoxide of chaetoglobosin A (2). Additionally, the structures of these known compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) were mainly elucidated by spectral data analysis as well as comparison with those reported in the literature. They were identified as chaetoglobosins A-G (2-8) [16][17][18], aureochaeglobosin B (9) [6], isochaetoglobosin D (10) [18], chaetoglobosin Fex (11) [16], penochalasin G (12) [19], armochaetoglobin G (13) [7], prochaetoglobosin I (14) [8], chaetoglobosins V b (15) [8] and Y (16) [18], respectively ( Figure 1).…”
Section: Structural Elucidationmentioning
confidence: 99%
“…Recently, a variety of cycloaddition heterodimers of cytochalasans with novel complicated architectures have been reported, exemplified by asperflavipine A [5], aureochaeglobosins A−C [6]. Chaetoglobosins, 10-(indol-3-yl)- [13]cytochalasans were recently reported to have cytotoxicity [6,7] and antibacterial activity [8], and have attracted great interest from both chemists and pharmacologists [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%